2020
DOI: 10.1111/tid.13413
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and kidney transplant recipients

Abstract: Background The novel coronavirus has become a global threat and healthcare concern. The manifestations of COVID‐19 pneumonia in transplant patients are not well understood and may have more severe symptoms, longer duration, and a worse prognosis than in immunocompetent populations. Aims This study proposed to evaluate the clinical characteristics of COVID‐19 pneumonia in kidney transplant recipients. Patients/Methods Clinical records, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…In our case series, we discussed the clinical characteristics and the outcomes of the first six kidney recipients with COVID-19 in our Hospital. The mortality rate in our patients was in line with similar previous studies [6,7]. Kidney recipients with COVID-19 developed even higher AKI than critically ill patients in Wuhan, China [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our case series, we discussed the clinical characteristics and the outcomes of the first six kidney recipients with COVID-19 in our Hospital. The mortality rate in our patients was in line with similar previous studies [6,7]. Kidney recipients with COVID-19 developed even higher AKI than critically ill patients in Wuhan, China [8].…”
Section: Discussionsupporting
confidence: 92%
“…Most notably, the mortality rate in our patients was 33.3%, which is nearly consistent with the previous studies Table 2 Laboratory findings of six kidney transplant recipients with COVID-19 on admission ALP alkaline phosphatase, ALT alanine transaminase, AST aspartate aminotransferase, COVID-19 coronavirus disease 2019, Cr creatinine, CRP C-reactive protein, eGFR estimated glomerular filtration rate, ESR erythrocyte sedimentation rate, Hb hemoglobin, LDH lactate dehydrogenase, WBC white blood cells a Urine protein is described as: negative, 0 mg/dL; trace, 15-30 mg/dL; 1 + , 30-100 mg/dL; 2 + , 100-300 mg/dL; 3 + , 300-1000 mg/dL; 4 + , more than 1000 mg/dL [6,7]. According to a recent review study, Moris et al [12], reported a cumulative mortality rate of 19.9% in kidney recipients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SO transplant were younger and had lower dependency level than the non-IS patients; despite this, their mortality odds was much higher. Most reports on COVID-19 transplant patients have been limited to small case series with conflicting results: while some have shown similar outcomes to the general population [ 33 , 34 ], others reported a very high mortality, as found by our study [ 35 , 36 ]. The largest study of SO transplant recipients reported data on 90 patients, of which 68 (76%) were hospitalized, with an in-hospital mortality of 24% [ 35 ].…”
Section: Discussionsupporting
confidence: 70%
“…Most notably, the mortality rate in our patients was 33.3%, which nearly is consistent with previous studies [6,7]. According to a recent review study, Moris, et al [10] reported a cumulative mortality rate of 19.9% in kidney recipients with COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…In our case series, we discussed the clinical characteristics and the outcomes of the rst six kidney recipients with COVID-19 in our Hospital. The mortality rate in our patients was in line with similar previous studies [6,7]. Kidney recipients with COVID-19 developed even higher AKI than critically ill patients in Wuhan, China [8].…”
Section: Discussionsupporting
confidence: 92%